An Appreciation of Organic Solid‐State Chemistry and Challenges in the Field of "Molecules, Materials, Medicines". Issue 1 (9th November 2016) - Jones, William
Abstract: Over many years, much of what has motivated a considerable amount of research in the general area of organic solid‐state chemistry concerns an understanding of how molecular packing within an organic solid affects its physical and chemical properties. Whilst the motivation for this understanding may have changed over time, the fundamental issues remain the same. An understanding of the effect of crystal attributes (e.g., polymorph, habit and particle size) on chemical, physical, photophysical and electronic properties is still vital to the development of organic solids with optimised properties. While progress has been made in analytical skills (including sophisticated developments in instrumentation), along with major developments in computational techniques, there are still many challenges. This paper, with a primary focus on pharmaceuticals, provides a brief, and not comprehensive, personal overview of the progress that has been made and has yet to be made. Amongst the chemists and crystallographers who have contributed significantly to the subject is Jack Dunitz and some of his seminal papers appear in several of the issues discussed.